Identifikasi Jenis Burung dan Kondisi Cuaca pada Tenggeran Buatan di Kawasan Restorasi Resort Sei Betung Taman Nasional Gunung Leuser (Identification of bird and weather on Artificial perch at Restoration Region Resort Sei Betung Gunung Leuser National - Akta Novita Damanik; Pindi Patana; Erni Jumilaty (Program studi Kehutanan USU, 2016)
Restoration in the resort area of Sei Betung covers 9.734 hectares. Various attempts were conducted to rehabilitate to the area, such as replanting or utilizing spreading seed agent of bird. The presence of a certain bird species, generally followthe preference on it’s habitat. This research observed what kind of bird perched on artificial perch and weather conditions in the area. The methodology used Ponctuels d'Abondance / Index Point of Abundant (IPA-Count), thas did not require extensive sampling place or a certain squares wide. This method consisted a series of points that spreaded randomly or in straight line. The results obtained the highest diversity of trees is 1,20, the highest bird abundance merbah cerucuk 31,67. Birds conducted their activities in temperature range between 26,50C - 310C and humidity around 70% and precipitation of 74,857mm. Keywords: Restoration, species of bird, temperature, humidity, rainfall